Institutional Interventions in Addressing Labour Scarcity – A Study on Labour Bank Initiatives in Thrissur District of Kerala - M. Anoop; N. Ajjan and K.R. Ashok (Agricultural Economics Research Review, 2014)
The study has highlighted an institutional intervention in the form of Labour Banks to address the scarcity of farm labourers in Kerala. The study has estimated the impact of Labour Banks on farm productivity, farm income, employment and standard of living of labourers. The study has used difference-in-difference estimation, partial budgeting technique and ANCOVA model for analysis. The Labour Bank member- labourers have depicted improvement in their standard of living, and their wage rate was higher by 21 per cent compared to that of non-members. The farmers who used Labour Bank service could achieve a rise of 0.92 t/ha in paddy productivity, and a profit of ` 11448/ha. The study has suggested replication of such models in other areas of the country also.